2005
DOI: 10.1161/circulationaha.104.515643
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Characteristics of Septal Hypertrophy in Patients With Hypertrophic Obstructive Cardiomyopathy and Moderate to Severe Symptoms

Abstract: Background-In hypertrophic obstructive cardiomyopathy, regional hypertrophy, myocardial replacement scarring, expanded interstitial fibrosis, and myocardial disarray can be found. The electrophysiological consequences of this substrate have not yet been investigated. Thus, the aim of this study was to assess the local electrophysiological characteristics of regional left ventricular (LV) septal hypertrophy. Methods and Results-In 9 patients with hypertrophic obstructive cardiomyopathy, electroanatomic voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The ST segment corresponds temporally to the plateau phase of the action potential, the repolarization of M cells is temporally aligned with the end of the T-wave, and repolarization of the epicardium is coincident with the peak of the T-wave [40]. Accentuation of spatial dispersion of repolarization due to an increase of transmural, transseptal, or apicobasal dispersion of repolarization can be expected in HCM which can manifest with varying patterns of hypertrophy (e.g., septal, apical, concentric) [41], regional ischemia due to microvascular dysfunction [42], and activation delays [43] due to fibrosis and ion channel/gap junction remodeling [44] which could alter the polarity of the ST segment and T-wave. This could explain our findings of (1) patients with repolarization abnormalities on EKG having greater impairment of cardiac mechanics than patients with normal EKGs and (2) similarity between the effect of classical strain pattern and non-specific ST depression/T-wave inversion on cardiac mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…The ST segment corresponds temporally to the plateau phase of the action potential, the repolarization of M cells is temporally aligned with the end of the T-wave, and repolarization of the epicardium is coincident with the peak of the T-wave [40]. Accentuation of spatial dispersion of repolarization due to an increase of transmural, transseptal, or apicobasal dispersion of repolarization can be expected in HCM which can manifest with varying patterns of hypertrophy (e.g., septal, apical, concentric) [41], regional ischemia due to microvascular dysfunction [42], and activation delays [43] due to fibrosis and ion channel/gap junction remodeling [44] which could alter the polarity of the ST segment and T-wave. This could explain our findings of (1) patients with repolarization abnormalities on EKG having greater impairment of cardiac mechanics than patients with normal EKGs and (2) similarity between the effect of classical strain pattern and non-specific ST depression/T-wave inversion on cardiac mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results, which suggest greater degree of electrical and structural remodeling in the interventricular septum, compared with other regions, are concordant with a previous invasive electrophysiological study that compared electrograms and local stimulus‐to‐V intervals in the septum and lateral wall in nine patients with HCM who demonstrated asymmetric septal hypertrophy. Using 3D electroanatomic mapping, Schumacher et al observed a high prevalence of fractionated, split, and low amplitude potentials associated with conduction slowing in the interventricular septum, but not in the lateral wall [20], indicating markedly higher prevalence of electrophysiologic abnormalities and heterogeneity in the septum in patients with HCM.…”
Section: Discussionmentioning
confidence: 99%
“…HCM histopathological features, such as replacement scarring, expanded interstitial fibrosis, and myocardial disarray, are associated with a marked prolongation of the bipolar endocardial potentials and with the occurrence of fractionated and split potentials at LV hypertrophic areas, 2 but also at RV septal sites 3 . Thus, local conduction disturbances within RV septum would be an ideal substrate for the development of reentry circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy (HCM) is a primary myocardial disease associated with a high risk of life-threatening ventricular tachyarrhythmias emanating from an electrical unstable myocardial substrate. 1,2 The most common ventricular arrhythmias observed include polymorphic ventricular tachycardia (VT) and fibrillation (VF) originating in the hypertrophic left ventricle (LV), while clinically stable monomorphic VT is less frequent. Local conduction disturbances have been observed also at right ventricle (RV) septal sites 3 that would be an ideal substrate for right ventricular reentrant monomorphic VT as reported here.…”
Section: Introductionmentioning
confidence: 99%